Prediction of low birth weight with hypoglycemia in glucose tolerance test - Hernández-Castro, Flavio; Berlanga-Garza, Anaís; Cruz-Gutiérrez, Mayela Diamantina; Soria-López, Juan Antonio; Villagómez-Martínez, Gabriel Edgar; Dávila-Escamilla, Iván Vladimir (Revista de Saúde Pública, 2021)
OBJECTIVE: Determine the value of the combination of fasting glucose less than the 10th percentile (FG < p10) during 75 gram oral glucose tolerance test (75g OGTT) with maternal characteristics to predict low birth weight (LBW) established by Intergrowth-21st tables. METHODS: Prospective cohort study of pregnant women who was underwent 75g OGTT between 24 and 28.6 weeks. The 10th percentile fasting glucose of the population was determined at 65 mg/dL and women with risk factors that could modify fetal weight, including those related to intrauterine growth restriction, were excluded. Two groups were formed: group FG < p10 and group with normal fasting glucose. The main finding was the diagnosis of LBW. The association between FG < p10, maternal characteristics and LBW was established by multivariate logistic regression. The predictive performance of the models constructed was evaluated by receiver operating characteristic (ROC) curve and area under the curve (AUC) analysis. RESULTS: 349 women were eligible for study, of whom 66 (18.91%) had FG < p10; neonates in this group had lower birth weights (2947.28 g and 3138.26 g, p = 0.001), higher frequencies of LBW (25% and 6.81%, p < 0.001) and of weights < 2500 g in term births (8.6% and 2.3%, p = 0.034). The basal prediction model consisted of nulliparity by achieving an AUC of 60%, while the addition of FG < p10 resulted in the significant improvement of the previous model (AUC 72%, DeLong: p = 0.005). CONCLUSIONS: In pregnant women without factors that could modify fetal weight, the predictive model created by combining FG < p10 during 75g OGTT with nulliparity was significantly associated with increased risk of LBW.